2017
DOI: 10.21608/jpp.2017.41987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Potassium Sources on Productivity and Quality of Pea under Conditions of Saline Soil

Abstract: This study was carried out during 2015 and 2016 seasons at a private Farm in Road Village in Sahl El-Husseiniya, Sharkia Governorate to study the influence of foliar spraying with three potassium sources at three concentrations from each of them i.e. potassium sulfate1,2 and 4 g/ L; potassium silicate at 1,2,and 4cm/L as well as potassium humate at 1,2 and 4 cm / L beside without foliar spraying (control) to reduce the bad effects salinity stress on growth, yield and quality of pea Master B cultivar under sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The enhancing effect of potassium silicate may be due to using SiO could be attributed to the benefit effects of Si in the plant, as an improve of the architecture for showing more erect leaves, which intercept higher solar luminosity increasing the photosynthetic efficiency and higher chlorophyll content.These results are in the same line of those obtained by Braga et al(2009), El-Hedek(2013) and Ismail et al(2017).…”
Section: -Effect Of Plant Stimulants Treatmentssupporting
confidence: 93%
See 1 more Smart Citation
“…The enhancing effect of potassium silicate may be due to using SiO could be attributed to the benefit effects of Si in the plant, as an improve of the architecture for showing more erect leaves, which intercept higher solar luminosity increasing the photosynthetic efficiency and higher chlorophyll content.These results are in the same line of those obtained by Braga et al(2009), El-Hedek(2013) and Ismail et al(2017).…”
Section: -Effect Of Plant Stimulants Treatmentssupporting
confidence: 93%
“…El-Hedek (2013) also found that spraying potassium silicate on leaves led to a significant improvement in the components of the wheat crop and an increase in its content of potassium, calcium and phosphorous ratios. In addition, Ismail et al (2017) found that spraying of pea plants with potassium silicatee at a rate of 4 cm / liter resulted in a significant increase and produced the uppermost average values for all studied vegetal growth parameters and their chemical components and components in leaves and seeds. Spraying of yeast has been found to increase the growth, productivity and quality of many vegetable crops (Abu Al-Nasr et al 2001;Kapil et al 2005 andFawzi, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…The beneficial impact of KH on the leaves photosynthetic pigments could be explained on the basis of that humic substances can directly or indirectly affect the physiological process of plant growth by promoting the uptake of macro-and micronutrients , affecting the biochemical substances , carrying nutrients and growth regulators and acting as hormones like substances (Verlindern et al, 2009). Yet , Ismail et al, (2017) and Dawood et al,(2019) attributed the enhancement effect of KH to the beneficial function of potassium on osmoregulation photosynthesis , transpiration, and translating of assimilates into sink organs . As a result, growth characteristics improve (Vani et al, 2017) .…”
Section: I-effect Of Treatments On Leaves Photosynthetic Pigmentsmentioning
confidence: 99%
“…Arkadiusz (2018) reported that spraying with 100 ppm to 300 ppm of potassium silicate in the growing medium had high effect at 4-leaf stage and positively effect at other stages of plant. Application of foliar spraying of pea plants with K-silicate at the rate of 228 ppm enhanced growth parameters, yield and yield components and nutrients contents (Ismail et al, 2017). Moustafa (2013) found that single and combined application of Ksilicate at 0.05 to 0.20% and royaljelly at 0.025 to 0.10%, greatly enhanced growth characters, pigments content and leaf content of N, P and K. Furthermore, Abdul-Qadir et al (2017) showed that when plants were treated with K-silicate, marked improvement in each of shoot fresh weight, shoot length, leaf area and leaf length was observed under water stress.…”
Section: Introductionmentioning
confidence: 98%